A Boundary Plane Approach to Map Hotspots for Achievable Soil Carbon Sequestration and Soil Fertility Improvement - Piikki, Kristin; Söderström, Mats; Sommer, Rolf; Silva, Mayesse Aparecida da; Munialo, Sussy; Abera, Wuletawu (MDPI, 2019)
Soil organic carbon (SOC) sequestration is important in the global carbon cycle and an integral part of many initiatives and policies to mitigate climate change. For efficient targeting of measures leading to SOC sequestration, it is necessary to know the actual SOC content (%) and a realistic target SOC content (in contrast to the saturation content, which may not be easily achievable) under local biophysical and socioeconomic conditions. We developed a new method for the practical assessment of achievable SOC sequestration concerning soil texture based on a non-linear boundary plane approach, also applicable for mapping of SOC sequestration hotspots. The method was tested at two spatial scales (a 125 km2 catchment and a 4 km2 sub-area of that catchment) in a region in Western Kenya characterized by smallholder farming. Moreover, we assessed the associated benefits of increasing the SOC content from a crop production perspective and found significant correlations between SOC and other soil properties (pH, cation exchange capacity, and various plant-available macro- and micronutrients). This indicates a possible improvement in soil fertility when the SOC content is raised to the modeled target levels, which should be attainable without major changes in land use or agricultural systems.